(untitled) (Ciudades, 2020)
The expansion of the production-accumulation system over the past three decades in the Comunidad de Madrid has taken place in a context of absence of a territorial model and with liberal land regulatory, which has facilitated the anthropization of the territory in search of locational advantages. Through an analysis of the regulatory framework and spatial competence levels, the paper shows the conditions and consequences of an urban expansion that has the flow of capital as its main objective.